Mere civility : disagreement and the limits of toleration - Bejan, Teresa M., 1984- (Harvard University Press, 2017)
Civility is often treated as an essential virtue in liberal democracies that promise to protect diversity as well as active disagreement in the public sphere. Yet the fear that our tolerant society faces a crisis of incivility is gaining ground. Politicians and public intellectuals call for "more civility" as the solution--but is civility really a virtue? Or is it something more sinister--a covert demand for conformity that silences dissent? Mere Civility sheds light on this tension in contemporary political theory and practice by examining similar appeals to civility in early modern debates about religious toleration. In seventeenth-century England, figures as different as Roger Williams, Thomas Hobbes, and John Locke could agree that some restraint on the wars of words and "persecution of the tongue" between sectarians would be required; and yet, they recognized that the prosecution of incivility was often difficult to distinguish from persecution.--